Effects of ethylenediamine on the physico-chemical properties of heavy oil. (19th May 2019) - Dong, Chi; Song, Kaoping; Lu, Jinhao; Yang, Erlong; Yao, Jixu
Abstract: As a type of organic base, ethylenediamine has a significant influence on the properties of the heavy oil, which can be used to emulsify the heavy oil under shear conditions. After 12 hours of shearing at the rate of 20r/min at the temperature of 60 °C, a volume heavy oil can be completely emulsified in 9 volume ethylenediamine solution with mass concentration of 5000 mg/L to form an O/W emulsion. Under the action of ethylenediamine, the interfacial tension is decreased, the Zeta potential is increased, the interfacial shear viscosity has a little change, and the stabilization of O/W emulsion is increased. The results can provide a reference for the study the mechanism of emulsification of heavy oil by using organic alkali.